2018
DOI: 10.1111/dom.13441
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin, a sodium‐glucose co‐transporter‐2 inhibitor, slows the progression of renal complications through the suppression of renal inflammation, endoplasmic reticulum stress and apoptosis in prediabetic rats

Abstract: Collectively, these findings indicate that dapagliflozin exerts renoprotective effects by alleviating obesity-induced renal inflammation, fibrosis, ER stress, apoptosis and lipid accumulation in the prediabetic condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 73 publications
8
52
0
1
Order By: Relevance
“…Reports of SGLT1 protein [80,84,103] and mRNA [83-85, 92, 93, 98] contents in PTs of T1D murine models are also contradictory while in T2D models only mRNA expression seems to be upregulated [22,90,92,98,100,[103][104][105][106]. SGLT2 has been studied in many models of diabetes, and the results suggest increased protein [32,67,84,85,90,94,99,[107][108][109][110][111] and mRNA [22,32,83,85,100,104,[106][107][108][109]112] contents and activity [108] despite some controversial results [85,93,98,100,105,113].…”
Section: Tubular Glucose Transporters In Animal Models Ofmentioning
confidence: 99%
“…Reports of SGLT1 protein [80,84,103] and mRNA [83-85, 92, 93, 98] contents in PTs of T1D murine models are also contradictory while in T2D models only mRNA expression seems to be upregulated [22,90,92,98,100,[103][104][105][106]. SGLT2 has been studied in many models of diabetes, and the results suggest increased protein [32,67,84,85,90,94,99,[107][108][109][110][111] and mRNA [22,32,83,85,100,104,[106][107][108][109]112] contents and activity [108] despite some controversial results [85,93,98,100,105,113].…”
Section: Tubular Glucose Transporters In Animal Models Ofmentioning
confidence: 99%
“…Intriguingly, a recent study reported that the HFD‐fed medaka exhibited enlarged glomeruli, dilated glomerular capillaries, and expanded mesangium, changes comparable to changes observed in humans with metabolic syndrome‐related glomerulopathy . To date, only a few studies demonstrated the beneficial effect of SGLT2Is on chronic renal injury in NASH animal models and elucidated the underlying mechanisms . The mechanisms include the renal inflammation, fibrosis, ER stress, apoptosis and lipid accumulation due to the increased renal expression of reactive oxygen species related to oxidative stress and TGF‐β1, type IV collagen, and fibronectin .…”
mentioning
confidence: 96%
“…Dapagliflozin is the first SGLT2 inhibitor used for anti-hyperglycemia therapy licensed by the FDA in 2014 ( Meng et al., 2008 ; Saeed and Narendran, 2014 ). Besides lowering blood glucose, dapagliflozin has protective roles in diabetic renal function by suppressing apoptosis, inflammation, and endoplasmic reticulum (ER) stress ( Jaikumkao et al., 2018 ). Intriguingly, a previous study revealed the ability of dapagliflozin to induce HIF-1α expression in renal cells ( Chang et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%